Available nitrogen and responses to nitrogen fertilizer in brazilian eucalypt plantations on soils of contrasting texture - Pulito, Ana Paula; Moraes Gonçalves, José Leonardo de; Smethurst, Philip J.; Arthur Júnior, José Carlos; Alvares, Clayton Alcarde; Tertulino Rocha, José Henrique; Huebner, Ayeska; Moraes, Luiz Fabiano de; Miranda, Aline Cristina [UNESP]; Kamogawa, Marcos Yassuo; Gava, José Luiz; Chaves, Raul; et al. (Mdpi Ag, 2015)
Eucalyptus plantations have seldom responded to N fertilization in tropical and subtropical regions of Brazil. This implies that rates of N mineralization have been adequate to supply tree needs. However, subsequent crop rotations with low N fertilization may result in declining concentrations of organic and potentially mineralizable N (N-0), and consequent loss of wood productivity. This study investigated (a) in situ N mineralization and N-0 in soils of eucalypt plantations in Sao Paulo state, Brazil; (b) tree growth responses to N fertilizer applied 6-18 months after planting; and (c) the relationships between N-0,N- other soil attributes and tree growth. We established eleven N fertilizer trials (maximum 240 kg ha(-1) of N) in E. grandis and E. grandis x urophylla plantations. The soil types at most sites were Oxisols and Quartzipsamments, with a range of organic matter (18 to 55 g kg(-1)) and clay contents (8% to 67%) in the 0-20 cm layer. Concentrations of N-0 were measured using anaerobic incubation on soil samples collected every three months (different seasons). The samples collected in spring and summer had N-0 140-400 kg ha(-1) (10%-19% total soil N), which were best correlated with soil texture and organic matter content. Rates of in situ net N mineralization (0-20 cm) ranged from 100 to 200 kg ha(-1) year(-1) and were not correlated with clay, total N, or N-0. These high N mineralization rates resulted in a low response to N fertilizer application during the early ages of stand growth, which were highest on sandy soils. At the end of the crop rotation, the response to N fertilizer was negligible and non-significant at all sites.